Designing and quality testing of “Digichip” virtual simulation software of Android platform for mobile-virtual learning supporting vocational mechatronics engineering - Titih Rejyasmito Hadi; Eko Marpanaji (Jurnal Pendidikan Vokasi, 2019)
Technology enhancement in any life aspects is undeniably crucial to face the globalization era. A strategic approach to touch any life aspect is gained through education. Supporting this educational long-term goal, this study aims to: (1) produce learning media in the form of a virtual-learning simulation software, which is capable of operation on mobile devices to facilitate mobile, portable, effective, economical, and operationally-safe learning; (2) test the developed software quality in terms of the functional aspects of suitability, maintainability, portability, and usability (ISO/IEC 25010). The subjects of this Research and Development (RD) study were class XI students of Mechatronics Engineering at SMTI Yogyakarta. The process of designing and testing software uses the V-model type Software Development Life Cycle (SDLC). Unit testing was done through the white-box technique with the base-path test, flowgraph, and independent path. The testing for integration, system, and acceptance used Black-box techniques. The study shows that: (1) V-models were used to design the "DigiChip" virtual simulation software to support virtual learning and mobile learning through the software development stage; (2) The software quality testing based on ISO/IEC 25010 shows that in the functional aspects suitability, all features function properly (very decent), its maintainability is of MI 84 (easy maintenance), it gains 100% portability, or can be operated on all Android OS kernels (very feasible), and its usability is 86.18% (very feasible) with Cronbach's Alpha 0.841 (good). Ninety percent of media experts and 100% of material experts consider that the developed software is very feasible.